2004
DOI: 10.1590/s0034-89102004000100007
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol drinking patterns by gender, ethnicity, and social class in Bahia, Brazil

Abstract: ObjectiveTo study patterns of alcohol consumption and prevalence of high-risk drinking. Methods A household survey was carried out in a sample of 2,302 adults in Salvador, Brazil. Cases of High-Risk Drinking (HRD) were defined as those subjects who referred daily or weekly binge drinking plus episodes of drunkenness and those who reported any use of alcoholic beverages but with frequent drunkenness (at least once a week). Results Fifty-six per cent of the sample acknowledged drinking alcoholic beverages. Overa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
42
3
34

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(95 citation statements)
references
References 21 publications
12
42
3
34
Order By: Relevance
“…4,8,21,22 In our study, men were likely to drink larger quantities of alcoholic beverages and more frequently than women. We have also found that men had higher prevalence rates of frequent binge drinking, namely heavy drinking, which is in agreement with the evidence from other studies conducted in Brazil 13,23 and other countries in Latin America, such as Mexico and Costa Rica. 12,13 Indeed, gender differences in alcohol use still remain.…”
Section: Discussionsupporting
confidence: 92%
“…4,8,21,22 In our study, men were likely to drink larger quantities of alcoholic beverages and more frequently than women. We have also found that men had higher prevalence rates of frequent binge drinking, namely heavy drinking, which is in agreement with the evidence from other studies conducted in Brazil 13,23 and other countries in Latin America, such as Mexico and Costa Rica. 12,13 Indeed, gender differences in alcohol use still remain.…”
Section: Discussionsupporting
confidence: 92%
“…The harmful alcohol consumption rate (31.0%) in our sample was similar to other Brazilian studies (11)(12) , and almost twice as high among men than among women, as frequently described in the literature (11)(12)(13) .…”
Section: Discussionsupporting
confidence: 91%
“…22,f The percentage of 39.6% of positive CAGE (alcohol abuse) was greater than that found in studies performed with other populations in Salvador. 1,3 This high percentage could be associated with cultural work aspects in this population that need to be further analyzed.…”
Section: Discussionmentioning
confidence: 96%